Lanthanum-induced electronic transition in hydride perovskites: A first-principles study of CsXH₃ (X = Sc, Y, La, Ac) (International Journal of Biology and Chemistry, 2026)
We studied the structural, mechanical, thermal, and electronic properties of cubic hydride perovskites CsXH₃ (X = Sc, Y, La, Ac) using first-principles DFT within the GGA-PBE and PAW schemes. The structural optimization and stability were studied using the third-order Birch-Murnaghan equation of state, and trends in the lattice parameters, bulk modulus, and compressibility were observed. The elastic constants and Voigt-Reuss-Hill approximations indicate mechanical stability. The phonon analysis shows no imaginary frequencies, which suggests dynamical stability. The thermal behavior is also characterized by a softening of the lattice with increasing cation size. Electronic structure results indicate metallic behavior of CsScH₃, CsYH₃, and CsAcH₃, while CsLaH₃ has a small band gap (~0.2 eV). Bonding shows that ionic character is present for CsLaH₃ with partial X–H covalency. This demonstrates the utility of cation engineering in hydride perovskites for hydrogen storage, conductive materials, and pressure-driven applications.Keywords: Hydride perovskites, Density Functional Theory, Mechanical properties, Electronic structure, Cation engineering.